Shear bond strength of a new composite for orthodontic use under different situations - Pithon, Matheus Melo (2015)
Aim: The aim of this study was to evaluate the shear bond strength of metallic orthodontic brackets bonded with Eagle Bond composite under different enamel surface conditions. Methods: Ninety bovine permanent lower incisors were divided into six groups (n = 15). In Group 1 (control) and Group 2 the brackets were bonded with XT primer/Transbond XT composite (3M Unitek) and Eagle Bond primer/Eagle Bond composite (American Orthodontic), respectively, according to the manufacturers’ recommendations. In the other groups, the brackets were bonded with Eagle Bond composite as follows: Group 3 had an enamel surface treated with Transbond Plus SelfEtching Primer; Group 4, bonding without application of Eagle Bond primer; Group 5, use of homogenized Eagle Bond composite; and Group 6, Eagle Bond primer/Eagle Bond composite applied on saliva/blood-contaminated dental surface. After bonding of the brackets, all specimens were tested in shear strength in an Emic universal testing machine at a crosshead speed of 0.5 mm/min. Results: There were no statistically significant differences among the groups (p > 0.05). A larger number of fractures were detected at the bracket/composite interface by the analyses of the Adhesive Remnant Index scores. Conclusions: It may be concluded that the modifications on the enamel surface did not compromise the shear bond strength of the composite Eagle Bond.